The E670G SNP in the PCSK9 gene is associated with polygenic hypercholesterolemia in men but not in women - Beil Frank U; Evans David (BMC, 2006)
Abstract Background Common genetic variants in the PCSK9 gene have been reported to be associated with both elevated and exceptionally low LDL levels. The association of a common haplotype, encompassing the E670G single nucleotide polymorphism, with LDL levels reported by Chen et al (J Am Coll Cardiol 2005; 45: 1644) was not confirmed by Kotowski et al (Am J Hum Genet 2006; 78:410-422). Methods The incidence of the E670G SNP was determined in 506 patients attending the lipid clinic, University Hospital, Hamburg. Results The frequency in men with polygenic hypercholesterolemia, 0.11 was significantly higher than in men with LDL<50th percentile, 0.03, p = 0.01. In women there was no difference in the allele frequencies between the two groups. Conclusion In a European population the E670G SNP in the PCSK9 gene is associated with increased LDL in men but not in women.